Microstructure evolution and room temperature fracture toughness of as-cast and directionally solidified novel NiAl-Cr(Fe) alloy. (May 2017) - Wang, Lei; Shen, Jun; Zhang, Yunpeng; Guo, Lanlan; Xu, Hengxin; Fu, Hengzhi
Abstract: The microstructure evolution and room temperature fracture toughness of as-cast and directionally solidified NiAl-Cr(Fe) alloy were investigated using OM, SEM, EDS, DSC and three-point bending tests. From the as-cast microstructure and DSC result, NiAl-34Cr-4Fe (at.%) is a eutectic alloy which consists of eutectic cells in different sizes. The half-baked mesh-like structure is observed at the cell center, and the radial emanating thicker or longer Cr(Fe) phases embedded within NiAl matrix are observed near or at the cell boundary. In the directional solidification process, the solid-liquid interface morphology has an evolutionary process of planar to cellular, even dendritic interface with increasing the withdrawal rates, and the eutectic cell and the microstructure at the cell center refines gradually. From the transverse microstructure, the characteristic of eutectic cell is similar to that of eutectic cell in as-cast alloy. It can be seen from the longitudinal colony/cell center that the broken (short) Cr(Fe) rods are observed at 6 μm/s, and they evolve to granular Cr(Fe) phases when the withdrawal rate increases further. Moreover, regardless of vacuum induction melting (as-cast) and directional solidification, NiAl-34Cr-4Fe (at.%) eutectic alloy possesses a poor fracture toughness due to the inferior brittleness of both NiAl and Cr(Fe) phases. Meanwhile, the crack propagation and fracture surface are observed to better understand the fracture behavior. Highlights: NiAl-34Cr-4Fe (at.%) is a eutectic alloy which consists of eutectic cells. Eutectic cell consists of central half-baked mesh and bordered rod-like structure. Directionally solidified microstructure is relatively regular at low withdrawal rate. Short rods evolve into granules, and mesh becomes finer with increasing the rate. Poor fracture toughness is due to the inferior brittleness of NiAl and Cr(Fe) phase.